Dampak Pelaksanaan UU Nomor 18 Tahun 1997 Terhadap Kinerja Keuangan Daerah: Studi Kasus di Kabupaten Pemalang - Mugiyatno, Mugiyatno (JKAP (Jurnal Kebijakan dan Administrasi Publik), 2001)
This research aims to understand the effect of policy implementation through Law No. 18 of /997 to the performance of local government finance. The case study is Pemalang regency. Contrary to the assumed policy goals, this research shovrs that during 2 years of its implementation in Pemalang the local original income (PAD) has virtually decreased. Although the nominal budget of the local government has increased, the PAD has contributed less. In effect, the policy has resulted in the decline of local government income from local taxation and charges, the overall fiscal effort and the degree of fiscal decentralization. It is recommended that the current policy problem should be addressed by determining the target of local taxes and charges with the real local potentials. The local government has to focus on the effective and efficient taxes that are linked to the local development budgets and the local gross domestic product.